Perceived image of Malaysian cuisine among students of UiTM Terengganu Branch, Campus Dungun / Aimi Sofia Razlan and Muhammad Imran Ismail - Razlan, Aimi Sofia; Ismail, Muhammad Imran (2019)
This study aims to investigate the perceptions of students of UiTM Terengganu branch, Dungun campus towards the image of Malaysian cuisine which reflects its identity. Through this study, it helps to explain the relationship between food characteristics and perceived image of Malaysian cuisine among the students. Descriptive research design by employing quantitative method through self- administered questionnaire was implemented for the purpose of this investigation. Questionnaires were successfully distributed to students of UiTM Dungun during for two consecutive weeks. All data were keyed-in into SPSS Version 25.0 and analyzed using statistical analysis. Results showed is correlation between perceptions and sensory characteristics towards perceiving the Malaysian cuisine. It was also found that there is significant relationship between food image and perceptions of students towards Malaysian cuisine. The authenticity dimension under cognitive food image is the most ideal criteria that students perceived to resembles Malaysian cuisine. Although many literatures stated that Malaysian cuisine lack its identity and do not have distinct characteristics of food, it is interesting to note that this study proved that Malaysian cuisine do have its own identity and distinct in term of the food authenticity. This characteristic could be utilized and harnessed to speak and define the concept of Malaysian cuisine, for a deeper understanding of the Malaysian cuisine and image in each individual’s mind.